The Concept of Mafhum al-Nash in the Thought of Nashr Hamid Abu Zaid: A Comparative Analysis with the Literal Approach of Khawarij - Wathani, Muhammad Fadhil; Sholeh, Muhammad Badrus; Salamah, Ika Hilmiatus; Sulaiman, Sulaiman; Amin, Nasihun; Wibowo, Taufik Awan (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2025)
This study examines the relationship between the thought of Nashr Hamid Abu Zaid and the ideology of Khawarij, focusing on the analysis of the concept of